AGE-RELATED MORPHOLOGICAL, FUNCTIONAL AND VISCOELASTIC CHANGES IN THE EYE AND DIAGNOSTIC CRITERIA OF PRIMARY OPEN ANGLE GLAUCOMA - M. A. Arapiev; D. N. Lovpache (Российский офтальмологический журнал)
The study, focused on morphological and functional changes in the eye during aging and early-stage glaucoma, included 112 people divided into 4 groups: the young control group I composed of 30 healthy young people (26.5 ± 5 years); the senior control group II involving 30 healthy elderly people (69.3 ± 4 years); group III composed of 30 glaucoma suspects (68.1 ± 6 years); and group IV consisting of 22 people with the early-stage of POAG (67.6 ± 5 years). All subjects received regular ophthalmic examination supplemented by examinations, laser scanning tomography, FDF and SAP perimetry, and dynamic applanation tonometry performed on the ORA analyzer. Aging and POAG have been shown to differ in the rate and the dynamics of morphological and functional changes. Also, our analysis has demonstrated that the assessment of age-related changes is important for early detection of the disease, when it has no clinical manifestations yet // Russian Ophthalmological Journal, 2016; 1: 5-11.